2017
DOI: 10.15275/rusomj.2017.0204
|View full text |Cite
|
Sign up to set email alerts
|

Salivary ferritin and iron as a marker and new discriminating indices between iron deficiency anemia and thalassemia: a meta-analysis

Abstract: Abstract:Purpose -We performed a meta-analysis of all eligible case-control studies published to date, to assess the association of salivary ferritin and iron with hematological disorders. Methods -We conducted Medline/PubMed and Scopus searches for papers published from January 1, 1980, through January 1, 2013. Data were merged the summary mean difference were estimated using either a random-effects model or a fixed-effects model. Results -There were 3 studies including 196 cases and 70 controls. There was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study by Kodati [13] reported lower levels of ferritin in serum and saliva of patients with iron deficiency anemia. Rahim [14] reported that salivary ferritin levels significantly increased in patients with thalassemia. The discrepancy between the two studies may be explained by the differences in sample size and, age of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Kodati [13] reported lower levels of ferritin in serum and saliva of patients with iron deficiency anemia. Rahim [14] reported that salivary ferritin levels significantly increased in patients with thalassemia. The discrepancy between the two studies may be explained by the differences in sample size and, age of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the use of saliva has come to be regarded as a reliable alternative method of ferritin assessment, one that is less invasive and offers a similar degree of sensitivity as serum [9,13]. In addition, it appears that changes in the salivary ferritin levels occur even before changes in the serum, meaning that saliva can be used as a valuable tool to assess the iron status [3,9,14]. The present study aimed to explore the correlation between the salivary and serum ferritin levels.…”
Section: Introductionmentioning
confidence: 99%